Selling the Ability to "Have It All": How Direct Selling Organizations Exploit Intensive Mothering Ideologies. (6th September 2021) - Rees, Mallory E
Abstract: Drawing on 27 interviews with consultants in the direct selling industry, this article argues that consultants' motivations to do stigmatized work with low financial rewards are tied to cultural pressures to adhere to intensive mothering ideologies. Some direct selling organizations in the United States are changing from a home party model—selling products out of homes—to a social commerce model—selling and recruiting using social media. Using a gendered organizations approach, these organizations portray themselves as feminine organizations, celebrating caregiving and allowing consultants—predominantly women—to reconcile work-family tensions through flexible work. Yet, this business model incentivizes a small number of financially successful consultants to train a much larger group to perform costly emotional labor for low pay. Consultants use the guilt tied to intensive mothering ideologies as a motivational tool in which they portray the cultural benefits of being a "good mother"—always available to and cultivating her children—as outweighing the emotional cost of doing stigmatized work that strains personal relationships. Rather than financially or emotionally supporting women, these organizations exploit women's investments in finding individualized solutions to work-family conflict and reaffirm racialized, classed, and sexualized ideologies.